La argumentación matemática una herramienta para el desarrollo en procesos de enseñanza-aprendizaje en la escuela (2024)
This research monograph aims to evaluate the development of mathematical argumentation processes in three cases of cycle 4 students through mathematical tasks. For this, the work is based on the definition of argumentation by Toulmin (2003), who highlights that this is a complex process given by 6 categories: statements, which contain the data prior to the conclusion, guarantees that allow the statements to be supported, support that correspond to a scientific support that supports the guarantee, a modal qualifier which is constituted by the word or set of words that give strength to the reasons (Toulmin, 2003, p. 95), all of this with the objective of giving A conclusion can later give way to a refutation that is part of the argument. Additionally, Schoenfeld (1992) allows us to talk about argumentation in mathematical tasks through the solution of problems proposed by Polya (1990). This theory confirms the use of argumentation as a tool in the teaching-learning of mathematics.